The Tribal Factor in Traditional Societies in South Asia (on the example of the Pashtun ethnic group) - Kanafyeva, Ш.Е. (Journal of Oriental Studies, 2024)
The Pakistani traditional society is versatile and its ethnic groups, such as Pashtuns, Balochs, Punjabis, Talpurs and others, are divided among themselves into several more clans and tribes, which have their own specific traditions and customs. Thus, it can be said that the national identity of Pakistan lacks a solid foundation that destabilizes the factor of uniting the country on one platform. In addition to this, Pakistani nationalism, based on Islamic identity and the Urdu language, is not fully shared by various ethnic groups, among which clans on the one hand and tribes on the other play an important role. Based on this, it can be stated that a number of ethnic and tribal nationalist movements may arise in the country, since the factors that cause them still exist. On the territory of Pakistan there is no single «nation», which is spread by the state of Pakistan. Pakistan is home to many clans, tribes, clans and ethnic groups that are very closely related to their origin, language and culture. After independence, Pakistan used a "nation-state" approach to create a unifying identity with very diverse ethnic identities, which turned out to be problematic. The all-inclusive approach has also provoked a number of inter-ethnic conflicts in different parts of the country. Based on the foregoing, this article discusses the main aspects of the bloodlines, tribes and clans of Pakistan on the example of the Pashtun ethnic group, which also strives to unite their own identity. Taking into consideration the mood factor of the Pashtun ethnic group, the article attempts a comprehensive analysis of the tribal factor in traditional society from the perspective of South Asia. The theoretical and methodological basis of the study was the results of field studies by foreign authors, as well as the work of domestic and Russian researchers. Keywords: Pakistan, tradition, society, tribe, relationship